2017
DOI: 10.1158/0008-5472.can-16-1916
|View full text |Cite
|
Sign up to set email alerts
|

Hypercholesterolemia Increases Colorectal Cancer Incidence by Reducing Production of NKT and γδ T Cells from Hematopoietic Stem Cells

Abstract: Obesity will soon surpass smoking as the most preventable cause of cancer. Hypercholesterolemia, a common comorbidity of obesity, has been shown to increase cancer risk, especially colorectal cancer. However, the mechanism by which hypercholesterolemia or any metabolic disorder increases cancer risk remains unknown. In this study, we show that hypercholesterolemia increases the incidence and pathologic severity of colorectal neoplasia in two independent mouse models. Hypocholesterolemia induced an oxidant stre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 45 publications
(45 reference statements)
3
58
0
1
Order By: Relevance
“…However, there are several reports on the association between tumorigenesis and lipid uptake in various types of cancers [ 23 , 24 ]. Hypercholesterolaemia, which is a common metabolic disorder in obese people, has been shown to increase the risk of gastroenterological cancers, and substantial epidemiologic evidence links hypercholesterolaemia to an increased risk of colorectal cancer [ 25 29 ]. However, the association between hypercholesterolaemia and prognosis in patients with GC has not been investigated adequately, although a previous study found that serum total cholesterol levels were inversely associated with the risk of stomach cancer in men [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are several reports on the association between tumorigenesis and lipid uptake in various types of cancers [ 23 , 24 ]. Hypercholesterolaemia, which is a common metabolic disorder in obese people, has been shown to increase the risk of gastroenterological cancers, and substantial epidemiologic evidence links hypercholesterolaemia to an increased risk of colorectal cancer [ 25 29 ]. However, the association between hypercholesterolaemia and prognosis in patients with GC has not been investigated adequately, although a previous study found that serum total cholesterol levels were inversely associated with the risk of stomach cancer in men [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…3a,b). Our previous studies had shown that Tet1 deficiency decreased their differentiation towards natural killer T cells and γδT cells 17 and increased the differentiation towards pro-inflammatory monocytes and macrophages. These results indicate that Tet1 deficiency alters the differentiation of HSCs to multiple cell lineages.…”
Section: Tet1 Deficiency Induces Loss Of Quiescence and Reduces The Lmentioning
confidence: 95%
“…The lentiviral particles were prepared according to the kit instructions. Freshly isolated KTSL cells were transduced with lentivirus for 24 hours and then selected with puromycin (2 μg/ml) (Santa Cruz Biotechnology, CA, USA) for 72 hours 17 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This increase in malignant events is not shared by mice that lack αβ T cells [11]. Similar protective effects by γδ T cells have been validated in models of colorectal cancer [12], malignant melanoma [13], B cell lymphoma [14] and prostate cancer [15]. These important contributions to tissue homeostasis and cancer immunosurveillance [16] have fuelled scientific interest to further explore the biology of γδ T cells and their potential for clinical translation [17,18].…”
Section: Introductionmentioning
confidence: 84%